ANALYZING DIFFERENT READINGS OF THE WORD LĀMASTUM AND INVESTIGATING ITS IMPACT ON INTERPRETATIVE PERCEPTIONS AND ENGLISH TRANSLATIONS - Askari, Seyed Kamel; Mousavi, Seyed Mohsen; Hasani, Seyed Mohamad (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2024)
This article discusses the difference in the reading of the word Lāmastum QS. Al-Nisa’: verse 43. It has resulted in the formation of two meanings; Shafi'i chose the recitation of Lamastum and stated that touching women invalidates ablution, Hanafi accepted the recitation of Lāmastum and declared that touching women does not invalidate ablution. Others have opinions for and against these two views. This research, which has been carried out in an analytic-descriptive method, has examined the difference in the readings of the word Lāmastum in this verse. The results of this study show that the difference in the reading of Lāmastum-Lamastum does not lead to a difference in meaning, but what causes different jurisprudential views of this verse is paying no attention to the ironical meaning and misunderstanding of the interpretation, which ultimately caused some translators suffice for the literal meaning and did not consider the ironic meaning of the word, and therefore, some English translators of the Holy Qur’an are not immune to this mistake.